PENGARUH PELATIHAN SUMBER DAYA MANUSIA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT PLN (PERSERO) WILAYAH SULUTTENGGO AREA MANADO - MEYLISA THESA WALUKOW; MIEKE RORING; JOHNY R.E TAMPI (JURNAL ADMINISTRASI BISNIS, 2016)
Abstract.This research was conducted to find out how big the influence of Training human resources (HR) against work productivity of employees At PT. PLN (Persero) Area of Manado.From the results of the research note that the training of human resources (HR) has a very strong Influence and is an important factor to increased Employee Productivity, PT. PLN (Persero) Area of Manado.Where human resources Training have an influence of 86.8% Employee to productivity and 13.2% set by factors that are not in this meticulous research such as leadership, compensation, work environment, placement, and other variables. It can be concluded that the training of HUMAN RESOURCES towards significantly influential work productivity of employees at PT. PLN (Persero) Area ofManado. This is because the Training of HUMAN RESOURCES is a strong factor to encourage morale or employee passion for placing certain activities in maximing the Productivity of work. Recommendations for the Management of HUMAN RESOURCES is maintained as well as improving the quality of training because training variables influence is dominant in affecting employee productivity, including through improvements in materials, methods and training tutuors so that employee productivity will increase. Keyword: Training, Human Resources, Employee Productivity